Extracellular matrix remodelling pathway in peripheral blood mononuclear cells from severe COVID-19 patients: an explorative study - Murphy, Sarah Louise; Balzer, Nora Reka; Ranheim, Trine; Sagen, Ellen Lund; Huse, Camilla; Bjerkeli, Vigdis; Michelsen, Annika E.; Finbråten, Ane-Kristine; Heggelund, Lars; Dyrhol-Riise, Anne Ma; Tveita, Anders; Holten, Aleksander Rygh; et al. (Frontiers in Immunology, 2024)
There is a reciprocal relationship between extracellular matrix (ECM) remodeling and inflammation that could be operating in the progression of severe COVID-19. To explore the immune-driven ECM remodelling in COVID-19, we in this explorative study analysed these interactions in hospitalised COVID-19 patients. RNA sequencing and flow analysis were performed on peripheral blood mononuclear cells. Inflammatory mediators in plasma were measured by ELISA and MSD, and clinical information from hospitalised COVID-19 patients (N=15) at admission was included in the analysis. Further, we reanalysed two publicly available datasets: (1) lung tissue RNA-sequencing dataset (N=5) and (2) proteomics dataset from PBCM. ECM remodeling pathways were enriched in PBMC from COVID-19 patients compared to healthy controls. Patients treated at the intensive care unit (ICU) expressed distinct ECM remodeling gene profiles compared to patients in the hospital ward. Several markers were strongly correlated to immune cell subsets, and the dysregulation in the ICU patients was positively associated with plasma levels of inflammatory cytokines and negatively associated with Bcell activating factors. Finally, our analysis of publicly accessible datasets revealed (i) an augmented ECM remodeling signature in inflamed lung tissue compared to non-inflamed tissue and (ii) proteomics analysis of PBMC from severe COVID-19 patients demonstrated an up-regulation in an ECM remodeling pathway. Our results may suggest the presence of an interaction between ECM remodelling, inflammation, and immune cells, potentially initiating or perpetuating pulmonary pathology in severe COVID-19.